Insights into Maxillary Sinus: Fungal Sinusitis - Umarov Odil Makhmudovich; Mirzakandov Elyor Erkinovich; Sanjar Usmonov (European Science Publishing, 2023)
The delayed diagnosis of chronic odontogenic sinusitis and the consequent untreated osteomyelitis of the upper jaw manifest varied clinical courses, even post-surgery, in cases of mycotic sinusitis. Recognizing the significance of timely diagnosis and treatment of odontogenic sinusitis stands paramount in expediting the overall recovery of patients and averting complications like osteomyelitis of the upper jaw. This article delves into the intricacies of mycotic sinusitis, emphasizing the critical role of prompt identification and management of odontogenic sinusitis. Highlighting the implications for patient's general well-being and complications prevention, this document serves as a crucial resource for medical professionals and individuals seeking comprehensive insights into managing odontogenic sinusitis effectively.
Keywords: Odontogenic Sinusitis, Mycotic Sinusitis, Chronic Sinusitis, Osteomyelitis, Upper Jaw Infections, Maxillary Sinusitis, Dental Infections, Sinus Surgery, Fungal Sinusitis, Nasal Complications.